The European Union and the issue of Genocide Condemnation and Prevention(The Case of the Armenian Genocide) - Teteyan, Arshaluys (History and Culture, 2025)
The problem of recognition and condemnation of 1915 Armenian Genocide by the member states of EU, European institutions especially European Parliament became the subject of various scientific studies. problem is that this studies emphasized and underlined the role of European Parliament and his resolutions and their impact on the political process. But even more important to examine not only European Parliemant resolutions, which usually have consultative significance consultative importance, but the action and steps of athers bodies of the Union their proportionality, policy of “two weights two measures”․ For the full and detailed study of EU’s policy regarding recognition and condemnation of genicides requires compare side by side the action and steps of others bodies of the Union towards Armenian Genocide, Holocaust committed against the Jewish people during World War II, Rwandan genocide, Srebrenica massacre and other crimes against humanity. Тhat’s how we can assess effectiveness of the mechanisms which have justified themselves, and also reveal the incomplete steps that left past crimes without impunity, thereby left the open path for future atrocities.